Pre-season energy status is associated with performance in competitive female long-distance runners - Williams, N.; De Souza, M. J.; Lundstrom, E. (10th International scientific conference on kinesiology. Book of abstracts, 2024)
Introduction Although chronic energy deficiency is prevalent in female athletes and linked to health outcomes described as the Female Athlete Triad, the impact on performance in weight bearing sports has not been fully elucidated. The primary purpose of this study was to explore the potential association between key indicators of adaptations to energy deficiency, i.e., the ratio of actual to predicted resting metabolic rate (RMR ratio) and serum total triiodothyronine on run time performance and on VO2max in college age female long-distance runners. We hypothesized that indications of energy deficiency would be negatively associated with running performance in a 5K competitive time trial.